TAILORING ENGLISH TEACHING MATERIALS: A CUSTOMIZED APPROACH USING THE ADDIE MODEL - Paramita, Paulina Erawati (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This report highlights the community service contribution through the presentation "Tailoring English Teaching Materials Using the ADDIE Model," delivered at the ARCENG International Scientific Research Conference in Istanbul, Türkiye, on April 20-21, 2024. The session aimed to equip educators with strategies for designing adaptable English teaching materials using the ADDIE instructional design framework. With the growing need for inclusive English instruction, structured methodologies are essential. The ADDIE model—Analysis, Design, Development, Implementation, and Evaluation— provides a systematic approach to material development, ensuring alignment with learner needs and educational goals. This presentation explored its application in English Language Teaching (ELT), drawing from research and practical experiences. The initiative sought to enhance teachers’ ability to create customized, relevant learning resources, foster collaboration, and contribute to global discussions on effective language education. The session featured interactive demonstrations of ADDIE’s practical applications, emphasizing cultural relevance, engagement, and adaptability. The presentation significantly impacted educators by providing practical tools, promoting authentic learning materials, and reinforcing continuous improvement through feedback. It also addressed key challenges, such as adapting materials for diverse learners and managing logistical constraints. Future efforts will focus on specialized workshops, open-access resources, institutional collaborations, digital integration, and further research on the long-term impact of tailored teaching materials. These initiatives aim to enhance English instruction globally, improving learner outcomes and educational quality.